Contingent sounds change the mental representation of one’s finger length - Ana Tajadura-Jiménez (Nature Portfolio, 2017)
Abstract Mental body-representations are highly plastic and can be modified after brief exposure to unexpected sensory feedback. While the role of vision, touch and proprioception in shaping body-representations has been highlighted by many studies, the auditory influences on mental body-representations remain poorly understood. Changes in body-representations by the manipulation of natural sounds produced when one’s body impacts on surfaces have recently been evidenced. But will these changes also occur with non-naturalistic sounds, which provide no information about the impact produced by or on the body? Drawing on the well-documented capacity of dynamic changes in pitch to elicit impressions of motion along the vertical plane and of changes in object size, we asked participants to pull on their right index fingertip with their left hand while they were presented with brief sounds of rising, falling or constant pitches, and in the absence of visual information of their hands. Results show an “auditory Pinocchio” effect, with participants feeling and estimating their finger to be longer after the rising pitch condition. These results provide the first evidence that sounds that are not indicative of veridical movement, such as non-naturalistic sounds, can induce a Pinocchio-like change in body-representation when arbitrarily paired with a bodily action.